Pengaruh Quality Of Work Life Dan Kepuasan Kerja Terhadap Employee Engagement Di Restoran Hokben Poris Paradise - Rosid, M Abdul; Fazira, Rabitha (JMB : Jurnal Manajemen dan Bisnis, 2024)
The purpose of this study is to find out the effect of quality of work life and job satisfaction on employee engagement at HokBen Poris Paradise restaurant. This research uses a quantitative approach. The population of this study is 30 employees of HokBen Poris Paradise. The sampling technique in this study is saturated sampling. The data analysis technique used is multiple linear regression.  The partial quality of work life results had a positive and significant effect on employee engagement indicated by a table count value (2,159>2,051) with a significance of 0.040. Partial job satisfaction had a positive and significant effect on employee engagement indicated by a table t count value (3.263>2,051) with a significance of 0.003. Simultaneously the quality of work life and job satisfaction had a positive and significant effect on employee engagement with a table F count of F (12,428>3.34) with a significance of 0.000. . Variable quality of work life and job satisfaction in explaining the company's value of 47.9% with R square 0.479 while 52.1% is influenced by other variables